2017
DOI: 10.1177/1178221817733736
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Substances Other Than Nicotine in Electronic Cigarettes Among College Students

Abstract: Introduction:Electronic cigarettes (e-cigarettes) have grown in popularity, especially among youth and young adults. Although e-cigarettes were originally intended to vaporize a liquid mixture containing nicotine, there appears to be an increasing trend in other substance use in e-cigarettes (OSUE).Materials and methods:Cross-sectional data from 1542 undergraduate college student e-cigarette users from a large Midwestern university were collected via online survey to assess prevalence of e-cigarette use, reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 35 publications
(66 reference statements)
4
49
3
1
Order By: Relevance
“…The present study also showed that marijuana users were significantly more likely to be past 30-day e-cigarette users, compared to non-users. Some studies suggest that vaping of cannabis extracts is becoming more common among marijuana users [19,35,36] due to its perception of being less harmful than the traditional burning to smoke methods [4], being easier to disguise due to reduced odours [35], and stimulating less throat irritation upon smoking [37]. Additionally, it is important to note that the current study utilizes results from a survey conducted in 2017, when cannabis was still considered an illegal substance in Canada.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study also showed that marijuana users were significantly more likely to be past 30-day e-cigarette users, compared to non-users. Some studies suggest that vaping of cannabis extracts is becoming more common among marijuana users [19,35,36] due to its perception of being less harmful than the traditional burning to smoke methods [4], being easier to disguise due to reduced odours [35], and stimulating less throat irritation upon smoking [37]. Additionally, it is important to note that the current study utilizes results from a survey conducted in 2017, when cannabis was still considered an illegal substance in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, e-cigarettes have been associated with a decline in overall health, including lung tissue damage, worse cardiovascular health outcomes and increased inflammatory responses [10][11][12]. Although none in Canada, some international studies have also shown positive associations between risky behaviors such as the use of illicit drugs, marijuana, alcohol and e-cigarette use [13][14][15][16][17][18][19][20][21][22]. Consequently, increased concerns have arisen among substance use researchers since recent e-cigarette designs have grown to accommodate illicit substances.…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation of opioids is typically achieved by heating the drug over a surface, often tin foil, and inhaling the resulting vapors (Jenkins et al, 1994;Strang et al, 1997). Recently, however, there have been reports of ENDS usage (vaping) for administering illicit substances, including opioid drugs (Kenne et al, 2017;Blundell et al, 2018;Breitbarth et al, 2018). The current popularity and acceptability of vaping, the covert and easily concealed designs of newer vaping devices, and the myriad flavorant options, which can potentially mask public use, make this latter method especially concerning.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it seems likely that the connection between nicotine and e-cigarettes was not a very close one and the changing perceptions of harm of nicotine might not translate into lower perceived harm of e-cigarettes. Indeed, while e-cigarettes were originally designed to deliver nicotine, they are now frequently used with other substances, such as a cannabis derivative, tetrahydrocannabinol (THC), particularly by young people [30][31][32]. THC-containing e-cigarettes recently received heavy media attention due to the outbreak of nationwide e-cigarettes-related lung injury in the U.S.…”
Section: Discussionmentioning
confidence: 99%